Kharif onion production through bulblets is remunerative - Singh, R K; Gupta, R P (Indian Horticulture, 2019)
Onion is most important vegetable crops grown in India having both food and medicinal values and widely cultivated for domestic consumption as well as for export. In the world, 85.80 million tonnes of onions are produced from 4.44 million ha area. India, being major onion-producing country, produces 193.56 lakh tonnes from 11.91 lakh ha, with a very low productivity of 16.24 tonnes/ ha. Because of its high export potential, it comes under cash crop apart from vegetable. About 55-60% of onion comes from rabi and 40-45% from kharif and late-Kharif seasons. Because of its special characteristics of pungency, it has more value than other vegetables crops. Apart from its importance for regular supply in domestic markets all over the country, it has got very good export potential for earning valuable foreign exchange for the country.